Different dissolution procedures for analysis of titanium(IV) oxide white pigment - Majcen, Nineta (Acta chimica slovenica, 1998)
Various ways of sample preparation for subsequent analysis of titanium(IV) oxide white pigment are presented. Three different procedures: digestion in various mediums, lithium metaborate fusion and pressure dissolution with hydrofluoric acid are precisely represented and considering accuracy, precision, blank values, time of analysis and general procedure's simplicity, the last procedure is undoubtedly the most appropriate one.
Keywords: anorganska kemija; pigmenti; raztapljanje; titanov dioksid